Low variability and absence of phenotypic correlates of Clock gene variation in a great tit Parus major population - Liedvogel, M; Sheldon, B (2010)
Studies of a range of taxa, including birds, have revealed latitudinal clines in allele length at the conserved Clock locus, a gene with known influences on behaviour and physiology. Such clines might reflect adaptation to seasonal variation, a suggestion supported by a recent within-population analysis of blue tits Cyanistes caeruleus, which found associations between Clock genotype and timing of breeding in females. To test the generality of this pattern, we sequenced the polymorphic poly-Q locus of the Clock gene in 521 female great tits Parus major, which were selected based on possession of extreme breeding phenotypes. In total, we identified five alleles with one allele accounting for 96% of allelic diversity in the sample set. Overall variability at the poly-Q locus was very low, and the spatial distribution of Clock alleles across Wytham was highly homogenous. Our data further provide no evidence for a connection between Clock genotype and reproductive timing phenotype in female great tits; further, we found no effect of Clock genotype on reproductive success. Hence, these results are in contrast to the pattern found for the sympatric blue tit population inhabiting the same woodlands, suggesting that phenotypic effects of Clock are not general in passerine birds. © 2010 The Authors.